KINERJA INOVASI MENUJU MAKING INDONESIA 4.0: ANALISIS PRAKTIK TQM DAN KNOWLEDGE MANAGEMENT - Masduki Asbari; Dewiana Novitasari; Muhamad Agung Ali Fikri (Journal Of Communication Education, 2021)
Abadi, iI., iJasiyah, iR., iDahniar, iN., i& iAlputila, iM. iJ. i(2019). iThe iconsciousness iof iexcellent iquality iservice ito iimprove ieffectiveness iof iTQM iand ikaizen-PDCA iquality imanagement. iIOP iConference iSeries: iEarth iand iEnvironmental iScience, i343(1), i12138.Abbas, iJ. i(2020). iSustainable iinnovation iin ismall imedium ienterprises: iThe iimpact iof iknowledge imanagement ion iorganizational iinnovation ithrough ia imediation ianalysis iby iusing iSEM iapproach. iSustainability i(Switzerland), i12(6). ihttps://doi.org/10.3390/su12062407Abdi, iK. i(2018). iThe ieffect iof iknowledge imanagement, iorganizational iculture iand iorganizational ilearning ion iinnovation iin iautomotive iindustry. iJournal iof iBusiness iEconomics iand iManagement, i19(1), i1–19. ihttps://doi.org/10.3846/jbem.2018.1477Acosta-Prado, iJ. iC. i(2020). iConditions iof iknowledge imanagement, iinnovation icapability iand ifirm iperformance iin iColombian iNTBFs: iA imeasurement iscale. iVINE iJournal iof iInformation iand iKnowledge iManagement iSystems, i51(2), i218–235. ihttps://doi.org/10.1108/VJIKMS-09-2019-0142Admiral, iChidir, iG., iAsbari, iM., iSupriatna, iH., i& iNovitasari, iD. i(2021). iLinking iEmployee iCoaching, iTeam iCommitment iand iPerformance: iEvidence ifrom iIndonesian iMSMEs. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i02(04), i22–34. ihttps://www.ijosmas.org/index.php/ijosmas/article/view/48Afriyie, iS., iDu, iJ., i& iMusah, iA. iA. iI. i(2019a). iINNOVATION iand iKNOWLEDGE iSHARING iof iSME iin iAN iEMERGING iECONOMY; iThe iMODERATING iEFFECT iof iTRANSFORMATIONAL iLEADERSHIP iSTYLE. iInternational iJournal iof iInnovation iManagement, i2050034, i1–26. ihttps://doi.org/10.1142/S1363919620500346Afriyie, iS., iDu, iJ., i& iMusah, iA. iA. iI. i(2019b). iInnovation iand iKnowledge iSharing iof iSME iin ian iEmerging iEconomy: iThe iModerating iEffect iof iTransformational iLeadership iStyle. iInternational iJournal iof iInnovation iManagement, i2050034, i1–26. ihttps://doi.org/10.1142/S1363919620500346Agistiawati, iE., i& iAsbari, iM. i(2020). iPengaruh iPersepsi iSiswa iatas iLingkungan iBelajar idan iPenguasaan iKosa iKata iTerhadap iKemampuan iBerbicara iBahasa iInggris iSiswa iSekolah iMenengah iAtas iSwasta iBalaraja. iEduPsyCouns: iJournal iof iEducation, iPsychology iand iCounseling, i2(1), i513–523.Agustina, iS. i(2019). iPeran iPemerintah idalam iRevolusi iIndustri i4.0. iKkp.Go.Id, i0–3. ihttps://kkp.go.id/itjen/page/1724-peran-pemerintah-dalam-revolusi-industri-4-070JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638252Akbariyeh, iH. i(2017). iThe iinfluence iof istrategic iorientation ion inew iproduct idevelopment: iMediating irole iinnovation, iknowledge imanagement iand iorganisational icapabilities: iAn iempirical iinvestigation. iInternational iJournal iof iBusiness iInnovation iand iResearch, i13(4), i502–518. ihttps://doi.org/10.1504/IJBIR.2017.085104Alanazi, iM. iH. i(2020). iThe imediating irole iof iprimary iTQM ifactors iand istrategy iin ithe irelationship ibetween isupportive iTQM ifactors iand iorganisational iresults: iAn iempirical iassessment iusing ithe iMBNQA imodel. iCogent iBusiness iand iManagement, i7(1). ihttps://doi.org/10.1080/23311975.2020.1771074Alkhazali, iZ. i(2019). iTqm ipotential imoderating irole ito ithe irelationship ibetween ihrm ipractices, iKm istrategies iand iorganizational iperformance: iThe icase iof iJordanian ibanks. iAcademy iof iStrategic iManagement iJournal, i18(3). ihttps://api.elsevier.com/content/abstract/scopus_id/85068468005Almarimi, iK. i(2019). iThe imediating ieffect iof iknowledge imanagement ion ithe irelation ibetween itqm iand ibanking iservice iperformance: ia ireview. iIn iInternational iJournal iof iAdvanced iScience iand iTechnology i(Vol. i28, iIssue i1, ipp. i554–576). ihttps://api.elsevier.com/content/abstract/scopus_id/85081188232Aman, iM., i& iAsbari, iM. i(2020). iPengembangan iAplikasi iHistory iGPS iTracker iBerbasis iWeb iPada iHandphone. iJIKEM: iJurnal iIlmu iKomputer, iEkonomi iDan iManajemen, i1(1), i17–29.Amin, iM., iAldakhil, iA. iM., iWu, iC., iRezaei, iS., i& iCobanoglu, iC. i(2017). iThe istructural irelationship ibetween iTQM, iemployee isatisfaction iand ihotel iperformance. iInternational iJournal iof iContemporary iHospitality iManagement, i29(4), i1256–1278. ihttps://doi.org/10.1108/IJCHM-11-2015-0659Amri, iW. iA. iA., iAsbari, iM., iGazali, iNovitasari, iD., i& iPurwanto, iA. i(2021). iThe iEffect iof iReligiosity iand iService iQuality ion iJob iSatisfaction: iA iCase iStudy iof iMSME iEmployees. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i1(01), i53–63.Ana, iN. i(2020). iService iQuality iModel i, iOrganizational iCommitment i, iand iTQM-Based iEducation iLeadership iin iOrganizational iDevelopment. i443(Iset i2019), i629–633.Asbari, iM. i(2011). iKepemimpinan iTransformasional: iLandasan iMenuju iWorld iClass iCompany.Asbari, iM., iBernarto, iI., iPurwanto, iA., iWijayanti, iL. iM., i& iHyun, iC. iC. i(2020). iThe iImpacts iof iLeadership iand iCulture ion iWork iPerformance iin iService iCompany iand iInnovative iWork iBehavior iAs iMediating iEffects.Asbari, iM., iHyun, iC. iC., iWijayanti, iL. iM., iImelda, iD., iYanthy, iE., iPurwanto, iA., iKusumaningsih, iS. iW., i& iPutra, iF. i(2020). iDiskursus iSoft iSkills idan iHard iSkills: iApa iyang iMembangun iInovasi iGuru iSekolah?Asbari, iM., i& iNovitasari, iD. i(2021). iPengaruh iAuthentic iLeadership iterhadap iMentalitas iSiap iBerubah idan iKinerja iPegawai iParuh iWaktu. iBusiness iManagement iJournal, i17(1), i73–88.Asbari, iM., iNovitasari, iD., i& iPebrina, iE. iT. i(2021). iPengaruh iMediasi iMental iKesiapan iuntuk iBerubah idan iWork-Family iConflict iterhadap iKinerja iKaryawan idi iMasa iPandemi iCovid-19. iMega iAktiva: iJurnal iEkonomi iDan iManajemen, i10(1), i24–38. ihttps://megaaktiva.umkendari.ac.id/index.php/Jurnal/article/view/123Asbari, iM., iNurhayati, iW., i& iPurwanto, iA. i(2019). ithe iEffect iof iParenting iStyle iand iGenetic iPersonality ion iChildren iCharacter iDevelopment. iJurnal iPenelitian iDan iEvaluasi iPendidikan, i23(2), i206–218. ihttps://doi.org/10.21831/pep.v23i2.281571JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-6382531Asbari, iM., iPurba, iJ. iT., iHariandja, iE. iS., i& iSudibjo, iN. i(2021a). iFrom iLeadership ito iInnovation: iManaging iEmployee iCreativity. iJurnal iManajemen iStrategi iDan iAplikasi iBisnis, i4(1), i143–154. ihttps://doi.org/https://doi.org/10.36407/jmsab.v4i1.287Asbari, iM., iPurba, iJ. iT., iHariandja, iE. iS., i& iSudibjo, iN. i(2021b). iMembangun iKesiapan iBerubah idan iKinerja iKaryawan: iKepemimpinan iTransformasional iversus iTransaksional. iJurnal iIlmiah iManajemen iDan iBisnis, i22(1), i54–71.Asbari, iM., iPurwanto, iA., iSudargini, iY., i& iFahmi, iK. i(2021). iThe iEffect iof iWork-Family iConflict iand iSocial iSupport ion iJob iSatisfaction: iA iCase iStudy iof iFemale iEmployees iin iIndonesia. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i1(01), i32–42.Asbari, iM., iPurwanto, iA., iWijayanti, iL. iM., iHyun, iC. iC., iKusumaningsih, iS. iW., iYanthy, iE., iPutra, iF., iWinanti, iW., iImelda, iD., i& iPramono, iR. i(2020). iPengaruh iHard iSkills, iSoft iSkills idan iMediasi iBudaya iSekolah iTerhadap iKapabilitas iInovasi iGuru idi iJawa iBarat. iJurnal iKependidikan: iJurnal iHasil iPenelitian iDan iKajian iKepustakaan iDi iBidang iPendidikan, iPengajaran iDan iPembelajaran, i6(1), i67–87.Asbari, iM., iTukiran, iM., iPurwanto, iA., iSantoso, iP. iB., iWijayanti, iL. iM., i& iHyun, iC. iC. i(2020). iMasih iRelevankah iPengukuran iGaya iBelajar iPada iPembelajaran iOnline? i(Sebuah iKajian iLiteratur iSistematis). iJournal iof iEngineering iand iManagement iScience iResearch i(JIEMAR), i1(2), i267–275. ihttps://journals.indexcopernicus.com/search/article?articleId=2660996Asbari, iM., iWijayanti, iL., iHyun, iC. iC., iPurwanto, iA., iSantoso, iP. iB., iBernarto, iI., iPramono, iR., i& iFayzhall, iM. i(2020). iThe irole iof iknowledge itransfer iand iorganizational ilearning ito ibuild iinnovation icapability: iEvidence ifrom iIndonesian iautomotive iindustry. iInternational iJournal iof iControl iand iAutomation, i13(1), i319–333. ihttp://sersc.org/journals/index.php/IJCA/article/view/5732Cavusgil, iS. iT., iCalantone, iR. iJ., i& iZhao, iY. i(2003). iTacit iknowledge itransfer iand ifirm iinnovation icapability. iJournal iof iBusiness i& iIndustrial iMarketing.Chang, iH. iT., iChou, iY. iJ., iMiao, iM. iC., i& iLiou, iJ. iW. i(2019). iThe ieffects iof ileadership istyle ion iservice iquality: ienrichment ior idepletion iof iinnovation ibehaviour iand ijob istandardisation. iTotal iQuality iManagement iand iBusiness iExcellence, i0(0), i1–17. ihttps://doi.org/10.1080/14783363.2019.1626708Chen, iI. iS. i(2017). iCritical iquality iindicators iof ihigher ieducation. iTotal iQuality iManagement iand iBusiness iExcellence, i28(1), i130–146. ihttps://doi.org/10.1080/14783363.2015.1050178Chiarini, iA. i(2011). iJapanese itotal iquality icontrol, iTQM, iDeming’s isystem iof iprofound iknowledge, iBPR, iLean iand iSix iSigma. iInternational iJournal iof iLean iSix iSigma.Chidir, iG., iKumoro, iD. iF. iC., iJohan, iM., iAsbari, iM., i& iNovitasari, iD. i(2021). iLearning idan iCoaching: iAnalisis iAnteseden iManajemen iKinerja iDosen. iCetta: iJurnal iIlmu iPendidikan, i4(2), i293–315.Chin, iW. i(1998). iThe iPartial iLeast iSquares iApproach ito iStructural iEquation iModeling i(E. iModern iMethods ifor iBusiness iResearch, iIn: iG. iA. iMarcoulides i(ed.)). iLawrence iErlbaum iAssociates iPublisher.Costa, iV. i(2016). iKey iknowledge imanagement iprocesses ifor iinnovation: ia isystematic iliterature ireview. iIn iVINE iJournal iof iInformation iand iKnowledge iManagement iSystems i(Vol. i46, iIssue i3, ipp. i386–410). ihttps://doi.org/10.1108/VJIKMS-02-2015-001772JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638254Creswell, iJ. iW., i& iCreswell, iJ. iD. i(2017). iResearch idesign: iQualitative, iquantitative, iand imixed imethods iapproaches. iSage ipublications.Darroch, iJ. i(2003). iDeveloping ia imeasure iof iknowledge imanagement ibehaviors iand ipractices. iJournal iof iKnowledge iManagement.Darroch, iJ. i(2005). iKnowledge imanagement, iinnovation iand ifirm iperformance. iJournal iof iKnowledge iManagement.Del iGiudice, iM., i& iDella iPeruta, iM. iR. i(2016). iThe iimpact iof iIT-based iknowledge imanagement isystems ion iinternal iventuring iand iinnovation: ia istructural iequation imodeling iapproach ito icorporate iperformance. iJournal iof iKnowledge iManagement, i20(3), i484–498. ihttps://doi.org/10.1108/JKM-07-2015-0257Ershadi, iM. iJ. i(2019). iMeasuring ithe iimpact iof isoft iand ihard itotal iquality imanagement ifactors ion icustomer ibehavior ibased ion ithe irole iof iinnovation iand icontinuous iimprovement. iTQM iJournal, i31(6), i1093–1115. ihttps://doi.org/10.1108/TQM-11-2018-0182Fikri, iM. iA. iA., iPramono, iT., iNugroho, iY. iA., iNovitasari, iD., i& iAsbari, iM. i(2021). iLeadership iModel iin iPesantren: iManaging iKnowledge iSharing ithrough iPsychological iClimate. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i2(03), i149–160.Fornell, iC., i& iLarcker, iD. iF. i(1981). iEvaluating iStructural iEquation iModels iwith iUnobservable iVariables iand iMeasurement iError. iJournal iof iMarketing iResearch, i18(1), i39. ihttps://doi.org/10.2307/3151312Ganguly, iA., iTalukdar, iA., i& iChatterjee, iD. i(2019). iEvaluating ithe irole iof isocial icapital, itacit iknowledge isharing, iknowledge iquality iand ireciprocity iin idetermining iinnovation icapability iof ian iorganization. iIn iJournal iof iKnowledge iManagement i(Vol. i23, iIssue i6). ihttps://doi.org/10.1108/JKM-03-2018-0190Ghozali, iI. i(2014). iStructural iEquation iModeling, iMetode iAlternatif idengan iPartial iLeast iSquare i(PLS) i(4th ied.). iBadan iPenerbit iUniversitas iDiponegoro.Gold, iA. iH., iMalhotra, iA., i& iSegars, iA. iH. i(2001). iKnowledge imanagement: iAn iorganizational icapabilities iperspective. iJournal iof iManagement iInformation iSystems, i18(1), i185–214.Hair, iJ. iF., iBlack, iW. iC., iBabin, iB. iJ., i& iAnderson, iR. iE. i(2010). iMultivariate iData iAnalysis i(7th ied.). iPearson iPrentice iHall.Hair, iJ. iF., iHult, iG. iT., iRingle, iC. iM., i& iSarstedt, iM. i(2014). iA iprimer ipartial ileast isquaresstructural iequation imodeling i(PLS-SEM). iSAGE iPublications.Hair, iJoe iF, iSarstedt, iM., iRingle, iC. iM., i& iMena, iJ. iA. i(2012). iAn iassessment iof ithe iuse iof ipartial ileast isquares istructural iequation imodeling iin imarketing iresearch. iJournal iof ithe iAcademy iof iMarketing iScience, i40(3), i414–433.Hair iJr, iJ. iF., iSarstedt, iM., iRingle, iC. iM., i& iGudergan, iS. iP. i(2017). iAdvanced iissues iin ipartial ileast isquares istructural iequation imodeling. isaGe ipublications.Honarpour, iA., iJusoh, iA., i& iMd iNor, iK. i(2018). iTotal iquality imanagement, iknowledge imanagement, iand iinnovation: ian iempirical istudy iin iR&D iunits. iTotal iQuality iManagement i& iBusiness iExcellence, i29(7–8), i798–816.Hung, iR. iY.-Y., iLien, iB. iY.-H., iFang, iS.-C., i& iMcLean, iG. iN. i(2010). iKnowledge ias ia ifacilitator ifor ienhancing iinnovation iperformance ithrough itotal iquality imanagement. iTotal iQuality iManagement, i21(4), i425–438.Hussein, iA. i(2019). iKnowledge imanagement iorientation ibehaviour iand iinnovation: iA ilesson ifrom iIndonesia icreative ieconomy isector. iInternational iJournal iof iSociotechnology iand iKnowledge iDevelopment, i11(1), i17–28.73JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638255ihttps://doi.org/10.4018/IJSKD.2019010102Hutagalung, iD., iAdmiral, iNuryanti, iY., iAsbari, iM., i& iNovitasari, iD. i(2021). iManaging iTacit iKnowledge iSharing: iFrom iCharismatic iLeadership ito iPsychological iSafety iClimate. iInovbiz: iJurnal iInovasi iBisnis, i9(1), i108–119. ihttps://doi.org/10.35314/inovbiz.v9i1.1888Johan, iM., iBudiadnyana, iG. iN., iAdmiral, iAsbari, iM., i& iNovitasari, iD. i(2021). iKepemimpinan iKarismatik idalam iPerspektif iKaryawan iUMKM: idari iMotivasi iIntrinsik ihingga iTacit iKnowledge iSharing. iEdumaspul: iJurnal iPendidikan, i5(1), i598–613. ihttps://ummaspul.e-journal.id/maspuljr/article/view/1303Jumiran, iNovitasari, iD., iNugroho, iY. iA., iSutardi, iD., iSasono, iI., i& iAsbari, iM. i(2020). iPengaruh iDimensi iKepemimpinan iTransformasional iterhadap iKepuasan iKerja idan iKomitmen iOrganisasional: iStudi iKasus ipada iDosen iPerguruan iTinggi iSwasta. iEduPsyCouns: iJournal iof iEducation, iPsychology iand iCounseling, i2(1), i600–621.Kim, iN., i& iShim, iC. i(2018). iSocial icapital, iknowledge isharing iand iinnovation iof ismall- iand imedium-sized ienterprises iin ia itourism icluster. iInternational iJournal iof iContemporary iHospitality iManagement, i30(6), i2417–2437. ihttps://doi.org/10.1108/IJCHM-07-2016-0392Masri, iR., i& iet ial. i(2018). ithe iManagement iDilemma ion ithe iDelivery iof iTacit-Explicit iKnowledge iin ithe iDiffusion iof iInnovation iTheory. iTurkish iOnline iJournal iof iDesign iArt iand iCommunication, i8(March), i686–692.Nadeak, iM., iWidodo, iA., iAsbari, iM., iNovitasari, iD., i& iPurwanto, iA. i(2021a). iUnderstanding ithe iLinks ibetween iCoaching, iOCB, iand iIndividual iPerformance iamong iMSME iEmployees. iInternational iJournal iof iSocial iand iManagement iStudies, i2(04), i65–80.Nadeak, iM., iWidodo, iA., iAsbari, iM., iNovitasari, iD., i& iPurwanto, iA. i(2021b). iUnderstanding ithe iLinks ibetween iCoaching, iOCB, iand iIndividual iPerformance iamong iMSME iEmployees. iInternational iJournal iof iSocial iand iManagement iStudies, i2(4), i65–80.Nguyen, iT. iP. iL., iTran, iN. iM., iDoan, iX. iH., i& iVan iNguyen, iH. i(2020). iThe iimpact iof iknowledge isharing ion iinnovative iwork ibehavior iof iVietnam itelecommunications ienterprises iemployees. iManagement iScience iLetters, i10(1), i53–62. ihttps://doi.org/10.5267/j.msl.2019.8.016Novitasari, iD., i& iAsbari, iM. i(2021). iLeaders iCoaching idi iSekolah: iApa iPerannya iterhadap iKinerja iGuru? iEdumaspul: iJurnal iPendidikan, i5(1), i580–597.Novitasari, iD., iAsbari, iM., iHutagalung, iD., i& iAmri, iL. iH. iA. i(2021). iMengelola iKomitmen iDosen: iAnalisis iPeran iModal iPsikologis idan iLeaders iCoaching. iValue : iJurnal iManajemen iDan iAkuntansi, i16(1), i198–213. ihttps://e-journal.umc.ac.id/index.php/VL/article/view/1845Novitasari, iD., iAsbari, iM., i& iPurwanto, iA. i(2020). iMaximizing iEmployee iPerformance: iAn iAnalysis iof iOrganizational iand iIndividual iFactors. iInternational iJournal iof iSocial iand iManagement iStudies, i1(1), i95–104.Novitasari, iD., iAsbari, iM., iPutra, iF., iKumoro, iD. iF. iC., i& iFikri, iM. iA. iA. i(2021). iTacit iKnowledge iSharing idi iSekolah iIslam: iAnalisis iKepemimpinan idan iIklim iKeamanan iPsikologis. iCetta: iJurnal iIlmu iPendidikan, i4(2), i138–162.Novitasari, iD., iHaque, iM. iG., iSupriatna, iH., iAsbari, iM., i& iPurwanto, iA. i(2021). iUnderstanding ithe iLinks ibetween iCharismatic iLeadership, iIntrinsic iMotivation iand iTacit iKnowledge iSharing iamong iMSME iEmployees. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i2(03), i1–13.Novitasari, iD., iHutagalung, iD., iAmri, iL. iH.74JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638256iA., iNadeak, iM., i& iAsbari, iM. i(2021a). iKinerja iInovasi idi iEra iRevolusi iIndustri i4.0: iAnalisis iKnowledge-Oriented iLeadership idan iKapabilitas iManajemen iPengetahuan. iEdukatif : iJurnal iIlmu iPendidikan, i3(4), i1245–1260. ihttps://doi.org/https://doi.org/10.31004/edukatif.v3i4.520Novitasari, iD., iHutagalung, iD., iAmri, iL. iH. iA., iNadeak, iM., i& iAsbari, iM. i(2021b). iKinerja iInovasi iDi iEra iRevolusi iIndustri i4.0: iAnalisis iKnowledge-Oriented iLeadership iDan iKapabilitas iManajemen iPengetahuan. iEDUKATIF: iJURNAL iILMU iPENDIDIKAN, i3(4), i1245–1260.Novitasari, iD., iHutagalung, iD., iSilitonga, iN., iJohan, iM., i& iAsbari, iM. i(2021). iMembangun iPerencanaan idan iKinerja iTim: iAnalisis iPengaruh iEfikasi iKolektif idan iIklim iKecerdasan iEmosional. iJKBM i(Jurnal iKonsep iBisnis iDan iManajemen), i7(2), i191–205. ihttps://doi.org/10.31289/jkbm.v7i2.5116Novitasari, iD., iSupiana, iN., iSupriatna, iH., iFikri, iM. iA. iA., i& iAsbari, iM. i(2021). iThe iRole iof iLeadership ion iInnovation iPerformance: iTransactional iversus iTransformational iStyle. iJIMFE i(Jurnal iIlmiah iManajemen iFakultas iEkonomi), i7(1), i27–36.Novitasari, iD., iSupriatna, iH., iAsbari, iM., iNugroho, iY. iA., i& iNadeak, iM. i(2021). iExploring ithe iImpact iof iTrust iin iLeader iand iKnowledge iSharing ion iEmployee iInnovation. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i02(03), i47–62. ihttps://www.ijosmas.org/index.php/ijosmas/article/view/30Nugroho, iY. iA., iPutra, iF., iNovitasari, iD., iAsbari, iM., i& iPurwanto, iA. i(2021). iDeveloping iInnovation iCapability: iBetween iIndividual iand iOrganizational iFactors. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i01(01), i74–88. ihttps://doi.org/https://doi.org/10.5555/ijosmas.v1i1.9Nurulin, iY., iSkvortsova, iI., iTukkel, iI., i& iTorkkeli, iM. i(2019). iRole iof iknowledge iin imanagement iof iinnovation. iResources, i8(2). ihttps://doi.org/10.3390/resources8020087Ofori, iD., iOsei, iA., iMensah, iS. iA., i& iAffum, iE. iK. i(2015). iInnovation iand iKnowledge iSharing : iA iNew iCompetitive iAdvantage iin ithe iMobile iTelecommunication iIndustry iin iGhana. i3(5), i157–163. ihttps://doi.org/10.11648/j.sjbm.20150305.14Ooi, iK. i(2015). iTQM ipractices iand iknowledge imanagement: ia imulti-group ianalysis iof iconstructs iand istructural iinvariance ibetween ithe imanufacturing iand iservice isectors. iTotal iQuality iManagement iand iBusiness iExcellence, i26(11), i1131–1145. ihttps://doi.org/10.1080/14783363.2014.914642Petcharit, iA. i(2020). iAn ianalysis iof itotal iquality imanagement i(TQM) iwithin ithe ithai iauto iparts isector. iInternational iJournal iof iOnline iand iBiomedical iEngineering, i16(2), i131–145. ihttps://doi.org/10.3991/ijoe.v16i02.11917Prajogo, iD. iI., i& iHong, iS. iW. i(2008). iThe ieffect iof iTQM ion iperformance iin iR&D ienvironments: iA iperspective ifrom iSouth iKorean ifirms. iTechnovation, i28(12), i855–863.Pramono, iT., iAsbari, iM., iSupriatna, iH., iNugroho, iY. iA., i& iNovitasari, iD. i(2021). iRahasia iInovasi iKaryawan iWanita idi iEra iDigital: iAnalisis iModal iPsikologis idan iDukungan iKepemimpinan. iValue : iJurnal iManajemen iDan iAkuntansi, i16(2), i1–17.Purwanto, iA., iAsbari, iM., iOng, iF., iPrameswari, iM., iSantoso, iP. iB., iHutagalung, iL., iBernarto, iI., iPrimahendra, iR., i& iPramono, iR. i(2020). iThe iEffect iof iForest iManagement iPEC, iFSC, iISO i38200:2018 ion iWood iIndustries iCompetitiveness: iEvidence ifrom75JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638257iIndonesia. iInternational iJournal iof iPsychosocial iRehabilitation, i24(6), i7018–7032.Purwanto, iA., iAsbari, iM., i& iSantoso, iP. iB. i(2020). iPengaruh iParenting iStyle idan iPersonality iGenetic iterhadap iPengembangan iPedidikan iKarakter iAnak idi iPAUD iIslamic iSchool. iQuality, i8(1), i51. ihttps://doi.org/10.21043/quality.v8i1.6606Purwanto, iA., iAsbari, iM., i& iSantoso, iT. iI. i(2021a). iAnalisis iData iPenelitian iManajemen iPendidikan: iPerbandingan iHasil iantara iAmos, iSmartPLS, iWarpPLS, idan iSPSS iuntuk iJumlah iSampel iKecil. iInternational iJournal iof iSocial, iPolicy iand iLaw i(IJOSPL), i1(01), i111–122.Purwanto, iA., iAsbari, iM., i& iSantoso, iT. iI. i(2021b). iAnalisis iData iPenelitian iMarketing: iPerbandingan iHasil iantara iAmos, iSmartPLS, iWarpPLS, idan iSPSS iuntuk iJumlah iSampel iBesar. iJournal iof iIndustrial iEngineering i& iManagement iResearch i(JIEMAR), i2(04), i216–227.Purwanto, iA., iAsbari, iM., i& iSantoso, iT. iI. i(2021c). iEducation iManagement iResearch iData iAnalysis: iComparison iof iResults ibetween iLisrel, iTetrad, iGSCA, iAmos, iSmartpls, iWarppls, iAnd iSPSS ifor iSmall iSamples. iNidhomul iHaq: iJurnal iManajemen iPendidikan iIslam, i6(2), i382–399.Purwanto, iA., iAsbari, iM., iSantoso, iT. iI., i& iHaque, iM. iG. i(2019). iMarketing iResearch iQuantitative iAnalysis ifor iLarge iSample: iComparing iof iLisrel, iTetrad, iGSCA, iAmos, iSmartPLS, iWarpPLS, iand iSPSS. iJurnal iIlmiah iIlmu iAdministrasi iPublik, i9(2), i355–372.Purwanto, iA., iAsbari, iM., iSantoso, iT. iI., iParamarta, iV., i& iSunarsi, iD. i(2020). iSocial iand iManagement iResearch iQuantitative iAnalysis ifor iMedium iSample: iComparing iof iLisrel, iTetrad, iGSCA, iAmos, iSmartPLS, iWarpPLS, iand iSPSS. iJurnal iIlmiah iIlmu iAdministrasi iPublik, i10(2), i518–532.Purwanto, iA., iAsbari, iM., iSantoso, iT. iI., iSunarsi, iD., i& iIlham, iD. i(2021). iEducation iResearch iQuantitative iAnalysis ifor iLittle iRespondents: iComparing iof iLisrel, iTetrad, iGSCA, iAmos, iSmartPLS, iWarpPLS, iand iSPSS. iJurnal iStudi iGuru iDan iPembelajaran, i4(2), i335–350.Purwanto, iA., iHidayat, iD., i& iAsbari, iM. i(2021). iWork-Family iConflict iDisaster: iFrom iOrganizational iCommitment ito iJob iSatisfaction. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i02(01), i86–92. ihttps://doi.org/https://doi.org/10.5555/ijosmas.v2i1.13Putra, iF., iAsbari, iM., iPurwanto, iA., iNovitasari, iD., i& iSantoso, iP. iB. i(2021). iLinking iSocial iSupport iand iPerformance iin iHigher iEducation. iInternational iJournal iof iSocial iand iManagement iStudies i(IJOSMAS), i1(01), i64–73.Sarstedt, iM., iRingle, iC. iM., iSmith, iD., iReams, iR., i& iHair iJr, iJ. iF. i(2014). iPartial ileast isquares istructural iequation imodeling i(PLS-SEM): iA iuseful itool ifor ifamily ibusiness iresearchers. iJournal iof iFamily iBusiness iStrategy, i5(1), i105–115.Silitonga, iN., iJohan, iM., iAsbari, iM., iHutagalung, iD., i& iNovitasari, iD. i(2021). iMengelola iKinerja iTim iEngineering: iDari iIklim iKecerdasan iEmosional ihingga iTeam iEfficacy. iValue: iJurnal iManajemen iDan iAkuntansi, i16(1), i172–187.Sudiyono, iR. iN., iGoestjahjanti, iF. iS., iAsbari, iM., iFayzhall, iM., iYani, iA., iWinanti, iYuwono, iT., iNurasiah, iYulia, iY., iSinggih, iE., i& iChidir, iG. i(2020). iMeningkatkan iKomitmen idan iKinerja iDosen : iApa iPeran iManajemen iPerguruan iTinggi ? iEduPsyCouns: iJournal iof iEducation, iPsychology iand iCounseling, i2(1), i337–352. ihttps://ummaspul.e-journal.id/Edupsycouns/article/view/489/283Suroso, iRiyanto, iNovitasari, iD., iSasono, iI., i&76JOCE IP Vol. 15 No. 2, SEPTEMBER 2021 ISSN : 1978-6875, E-ISSN : 2686-638258iAsbari, iM. i(2021). iEsensi iModal iPsikologis iDosen: iRahasia iKreativitas idan iInovasi idi iEra iEducation i4.0. iEdumaspul i- iJurnal iPendidikan, i5(1), i437–451. ihttps://ummaspul.e-journal.id/maspuljr/article/view/1240Sutardi, iD., iNovitasari, iD., iAsbari, iM., iSilitonga, iN., iNugroho, iY. iA., iHutagalung, iD., iMustofa, iChidir, iG., iBasuki, iS., i& iYuwono, iT. i(2020). iPengaruh iWork-Family iConflict, iStres iKerja idan iSocial iSupport iterhadap iKepuasan iKerja: iStudi iKasus ipada iGuru iWanita idi iTangerang. iEduPsyCouns: iJournal iof iEducation, iPsychology iand iCounseling, i2(1), i482–498. ihttps://ummaspul.e-journal.id/Edupsycouns/article/view/513Ullah, iI. i(2019). iExamination iof iknowledge imanagement iand imarket iorientation, iinnovation iand iorganizational iperformance: iInsights ifrom itelecom isector iof iPakistan. iKnowledge iManagement iand iE-Learning, i11(4), i522–551. ihttps://doi.org/10.34105/j.kmel.2019.11.027Wiratna, iS. i(2014). iMetodologi iPenelitian. iIn iPustaka iBaru. iPT. iPustaka iBaru.Yolanda, iO., iPurwanto, iA., iPramono, iY., iAsbari, iM., iBudi iSantoso, iP., iMayesti iWijayanti, iL., iChi iHyun, iC., i& iSetyowati iPutri, iR. i(2020). iStudi iEksploratif iDampak iPandemi iCOVID-19 iTerhadap iProses iPembelajaran iOnline idi iSekolah iDasar.Yusr, iM. iM. i(2016). iInnovation icapability iand iits irole iin ienhancing ithe irelationship ibetween iTQM ipractices iand iinnovation iperformance. iJournal iof iOpen iInnovation: iTechnology, iMarket, iand iComplexity, i2(1), i6.Yusr, iM. iM., iMokhtar, iS. iS. iM., iOthman, iA. iR., i& iSulaiman, iY. i(2017). iDoes iinteraction ibetween iTQM ipractices iand iknowledge imanagement iprocesses ienhance ithe iinnovation iperformance? iInternational iJournal iof iQuality i& iReliability iManagement.